The incidence of paresthesia and neurologic complications after lower spinal thoracic puncture with cut needle compared to pencil point needle. Study in 300 patients - Imbelloni, Luiz Eduardo; Pitombo, Patricia Falcão [UNESP]; Ganem, Eliana Marisa [UNESP] (OMICS International, 2010)
Background: Anesthesiologists are reluctant to considerer higher levels for spinal anesthesia largely due to direct threats to spinal cord. Paresthesias are relatively common during spinal needle insertion; however, the clinical significance of the paresthesia is unknown. The main objective of this prospective study was to evaluate the incidence of paresthesia and neurologic complications after lower thoracic spinal anesthesia with a cut needle compared to a pencil point needle. Methods: Low thoracic spinal puncture (T10-T11) was performed in 300 patients in elective surgery using different techniques in this single-blind prospective trial. Patients randomized to 2 groups: group 1, subarachnoid puncture using a cut needle without introducer and group 2, subarachnoid puncture using a pencil point needle with introducer. In both groups patients were in the lateral or sitting position. Results: Paresthesias occurred in 20/300 (6.6%) of patients. Seven patients experienced a paresthesia with cut needle compared with 13 patients with pencil point, without statistical difference. All paresthesias were transient. No neurologic complications were observed in all patients during this study. Conclusions: Our data suggest that all transient paresthesia are transitory. Lower thoracic puncture is safe. Traumatic injury to the spinal cord is a rare cause of neurologic deficits in the thoracic puncture. © 2010 Imbelloni LE, et al.
Keywords: Anesthesia; Needles; Paresthesia; Spinal; Subaracnoid